Infekční zánět symfýzy (symphysitis pubis purulenta): pět kazuistik a přehled literatury - Fridrich, F; Báča, V; Džupa, V (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2016)
Purulent inflammation of the pubic symphysis is a rare condition involving the symphysis and parasymphyseal parts of the pubic bones. It is usually found in immuno-compromised patients and its most frequent cause is Staphylococcus aureus. Conservative treatment is based on long-term administration of antibiotics and has been efficient, as reported, in about 50% of the patients. The authors treated five patients with a late diagnosis of purulent infection of the pubic symphysis in whom the antibiotic therapy had to be completed by surgical intervention. Three patients undergoing surgery with removal of the infected necrotic tissue healed fast and well. One patient required repeated surgery because of recurrent purulency; eventually, the infection cleared up. One patient was treated only conservatively because she refused surgical treatment. Consequently, pubic diastasis developed and she suffered from persistent pelvic pain. One year after treatment her condition became complicated by pelvic fracture following a fall. The patient refused surgery again. However, the development of non-union and progression of complaints made her agree to a surgical treatment; fixation of the non-union had a satisfactory outcome. In the literature, infection in the symphysis region is referred to by several different names. One - in the authors' opinion incorrect use - is "arthritis" (septic arthritis of the pubic symphysis; pubic symphysis septic arthritis; infectious osteoarthritis of the pubis). Another term is "osteomyelitis" (acute pubic osteomyelitis; pubic osteomyelitis; osteomyelitis of the pubis; osteomyelitis pubis; osteomyelitis of the pubic symphysis; osteomyelitis of the symphysis pubis). None of the names shows clearly whether it is primary an infection of the symphysis or of the parasymphyseal bone. A combination of the term "osteitis" with "infectious" (infectious osteitis pubis) is an attempt to distinguish purulent symphysitis pubis from osteitis pubis. The authors completed both the Czech and English title of this paper with the Latin designation symphysis pubis purulenta. A possibility of using a new name, such as "pubosymphysitis", in analogy to "spondylodiscitis" can also be discussed. However, the use of simple terms "infection of symphysis" or "infection of pubic symphysis" seems to be most practicable. Based on the experience with the treatment of five patients with infection of the pubic symphysis, the authors suggest that the late phase with abscess formation or purulent discharge should be managed by surgery. This treatment has good clinical outcomes although it may be complicated by slow healing of soft tissues around the symphysis and instability of the anterior pelvic segment with its sequelae. Key words: infection of the symphysis, infection of the pubic symphysis, septic arthritis of the pubic symphysis, pubic osteomyelitis.
Keywords: Male; Treatment Outcome; infekční artritida; Pubic Symphysis; Staphylococcal Infections; Combined Modality Therapy; Humans; mužské pohlaví; Female; artroskopie; stafylokokové infekce; Arthritis, Infectious; ženské pohlaví; Arthroscopy; Anti-Bacterial Agents; kombinovaná terapie; symphysis pubica; lidé; antibakteriální látky; výsledek terapie